PENULISAN FUQAHA MENGENAI HISBAH DAN PERANANNYA DI DALAM MEREALISASIKAN HUKUM FIQH - Che Yaacob, Ahmad (Jurnal Syariah, 2019)
Al-l-fisbah is one of the enforcement units in Islam. It is to enjoin al-Ma 'ruf and to forbid al-Munkar. This article elaborates the development of this institution from the beginning of Islam to the medieval age. The writer discusses two types of Ifisbah manuals i.e. theory and practice, written by ulama' and those involved directly with it and also the scope of mu~tasib jurisdiction.